2018
DOI: 10.1055/s-0038-1667139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Dog, Surgeon and Surgical Procedure Variables on Improvement in Eight-Week Static Weight-Bearing following Tibial Plateau Levelling Osteotomy

Abstract: Objective The purpose of this article was to compare the effect of surgeon and tibial plateau levelling osteotomy (TPLO) procedure variations on the outcome of TPLO in naturally occurring cranial cruciate ligament disease. Materials and Methods Records from 142 dogs that had a TPLO procedure were reviewed for information regarding surgical procedure, status of meniscus at the time of surgery, surgeon identity, ACVS diplomate or resident, meniscal release, progression of healing at the progress eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Both groups had increases in percent weight bearing during the period of forced activity restriction, with the difference between the two groups nearing significance (P = 0.10). Percent weight bearing with use of stance analysis has been evaluated for dogs undergoing TPLO [16,17]. A recent publication reported no effect on weight bearing when evaluating surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, postoperative TPA, and initial TPA in dogs undergoing TPLO [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups had increases in percent weight bearing during the period of forced activity restriction, with the difference between the two groups nearing significance (P = 0.10). Percent weight bearing with use of stance analysis has been evaluated for dogs undergoing TPLO [16,17]. A recent publication reported no effect on weight bearing when evaluating surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, postoperative TPA, and initial TPA in dogs undergoing TPLO [16].…”
Section: Discussionmentioning
confidence: 99%
“…Percent weight bearing with use of stance analysis has been evaluated for dogs undergoing TPLO [16,17]. A recent publication reported no effect on weight bearing when evaluating surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, postoperative TPA, and initial TPA in dogs undergoing TPLO [16]. Our study showed similar increases in percent of weight supported in the affected hind limb in dogs treated with Fortetropin1 than the placebo in the period of forced exercise restriction (week 0 to week 8), with the Fortetropin1 group nearly reaching significance over the placebo group (P = 0.10).…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic research, it is currently common to evaluate dynamic musculoskeletal function of the dogs using kinetic or kinematic gait analysis [19][20][21]. Moreover, measurement of static weight bearing [22,23] as well as measurement of range of motion in joints [24,25] are often performed. Although several studies have reported various radiographic abnormalities in English bulldogs [1,9,10,[14][15][16], research evaluating the musculoskeletal function of the dogs and specifically the association of orthopaedic findings with dogs' weight bearing and locomotion is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggests that postoperative complications impact TPLO mRUST scores and potentially bone healing. A previous study looked at static force on a limb following TPLOs and showed that complications had no effect on weight‐bearing at recheck 28 . Additional mechanisms beyond Wolff's law may therefore be at play, but prospective studies of TPLO mRUST scoring coupled with force plate analysis would be necessary to evaluate this further.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study looked at static force on a limb following TPLOs and showed that complications had no effect on weight-bearing at recheck. 28 Additional mechanisms beyond Wolff's law may therefore be at play, but prospective studies of TPLO mRUST scoring coupled with force plate analysis would be necessary to evaluate this further. Second, TPLO mRUST scores and therefore bone healing was greater at recheck postoperative radiographs in cases with higher lameness scores at presentation (P = .049).…”
Section: Discussionmentioning
confidence: 99%